Is Australia "Fair Dinkum" about drug education in schools? - Milford, Richard (Taylor and Francis, 2007)
School drug education is seen by governments as an ideal prevention strategy because it offers the potential to stop use by the next generation. Australian schools substantially expanded drug education during the 1960s in response to rising use by young people, and in 1970 the first national drug education program was launched. In the mid 1990s the level and quality of drug education increased noticeably. Unfortunately, subsequent national initiatives have failed to capitalise on the gains made during this period. Some, good quality, independent research, such as the Gatehouse Project and the School Health and Alcohol Harm Reduction Project (SHAHRP), have been conducted in Australia. However, national level momentum is being lost, because there is little commitment to the development of evidence based mass programs. In this climate drug education has become vulnerable to short term decision making that emphasises palatable, policy driven outcomes and focuses on strategies designed to bolster the legitimacy of these goals. So is Australia 'Fair Dinkum' about drug education in schools? There is a history of innovation, and past programs have left behind pockets of expertise, but the challenge is to continuously invest in methods with evidence of success, rather than settle for cyclical programs driven by the political and moral palliatives of the day. To do less is to fail the young people of Australia.